Modification of the magnetic mineralogy in basalts due to fluid–rock interactions in a high‐temperature geothermal system (Krafla, Iceland) - Oliva‐urcia, Belén; Kontny, Agnes; Vahle, Carsten; Schleicher, Anja M. (Geophysical Journal International, 2011)
Peer Reviewed http://deepblue.lib.umich.edu/bitstream/2027.42/86918/1/j.1365-246X.2011.05029.x.pdf